Forced Displacement in the Great Lakes Region - World Bank Group; United Nations High Commissioner for Refugees (Washington, DC, 2015)
At the end of 2013, there were about 3.3 million people who remained forcibly displaced within the Great Lakes Region (GLR) of Africa. Of these, 82 percent were internally displaced persons (IDPs) and 18 percent refugees; 64 percent were under 18 years old. This Report analyzes the extent, causes, and character of this forced displacement, with particular attention to certain situations.